MENINGKATKAN PRESTASI BELAJAR SISWA KELAS IX DI SMP NEGERI 4 KOTA TEBING TINGGI DALAM PRAKTIK PENDALANGAN MENGGUNAKAN MEDIA NASKAH - Benedikta Hutabarat (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to improve the achievement of class IX students at SMP Negeri 4 Kota Tebing Tinggi in the practice of mastering using media manuscripts. Based on the results of the evaluation that has been carried out, quantitatively there is an increase in the learning achievement of students of class IX on the subject of Cultural Arts in Pedestrian Practice SMP N 4 Tebing Tinggi, both individually and in groups. The increase reached 10% to 17.33% individually, while in groups it increased to 11.83%. in action (cycle) I (first). Whereas in the second (second) action (cycle) the individual increase reached between 34.28% to 46.66%, and in groups increased to 35.65%. Based on the data above, it can be concluded that the use of manuscript media is very effective to improve the learning achievement of class IX students in Pedal Art Skill Competency Practice Pedestal in SMP N 4 Tebing Tinggi.Keywords: Improve learning achievement, art of mastering